2017
DOI: 10.1242/bio.022210
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 signalling mediates PI3K-dependent large lipid droplet accumulation inDrosophilaovarian nurse cells

Abstract: Insulin and insulin-like growth factor signalling (IIS), which is primarily mediated by the PI3-kinase (PI3K)/PTEN/Akt kinase signalling cassette, is a highly evolutionarily conserved pathway involved in co-ordinating growth, development, ageing and nutrient homeostasis with dietary intake. It controls transcriptional regulators, in addition to promoting signalling by mechanistic target of rapamycin (mTOR) complex 1 (mTORC1), which stimulates biosynthesis of proteins and other macromolecules, and drives organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…It is also related to lipid metabolism in many cancers such as gastric cancer [ 57 ], hepatocellular carcinoma [ 58 ] and breast cancer [ 59 ]. Recent reports have showed that the activation of the PI3K signaling pathway is linked to lipid synthesis [ 43 ] and lipid droplet accumulation [ 60 ] in OC. In our study, we proved that FOXC2, STC1 and ITGB6 could activate the PI3K signaling pathway in OC cells and that this process may be related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is also related to lipid metabolism in many cancers such as gastric cancer [ 57 ], hepatocellular carcinoma [ 58 ] and breast cancer [ 59 ]. Recent reports have showed that the activation of the PI3K signaling pathway is linked to lipid synthesis [ 43 ] and lipid droplet accumulation [ 60 ] in OC. In our study, we proved that FOXC2, STC1 and ITGB6 could activate the PI3K signaling pathway in OC cells and that this process may be related to lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In Crassostrea gigas , PTEN is involved in insulin pathway in gonads and plays a critical role in reproduction [ 65 ]. In Drosophila , loss of PTEN is related to IIS/mTORC1 signalling, which is important for oogenesis [ 66 ]. In the present study, F3nRR showed significantly low expression levels of PTEN , which may have caused F3nRR normal fertility through regulation of oogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamentally, though, the inception and “normal” progression of the mutant condition or the diseased state can be closely followed, for example, the relationship between sleep and metabolism alterations via insulin signaling [ 219 221 ]. Unfortunately, to this day few studies have consciously addressed these chronic aspects of diabetes, although some do compare flies at different stages, like during oogenesis [ 222 ], or pupariation [ 223 ], or neurite remodeling [ 224 ], or adult stages [ 225 ].…”
Section: Invertebrate Insulin Signalingmentioning
confidence: 99%